Assessing the potential of diaspora tourism - Roberts, Sherma (2012)
Maps the contribution associated with migrant travel back to their native home for the purpose of leisure, and as a corollary proposes related strategic imperatives that Caribbean tourism policy and decision makers can engage, in the pursuit of this segment.